Exploring The Meaning of Love and Longing for Poetry in Ibn Arabi's Diwan Tarjuman Al-Ashwaq - Nurfaiza, Salma (Jurusan Sastra Indonesia, 2023)
This article aims to analyze the meaning of love and longing for literary works in the form of poems contained in the Diwan Tarjuman Al-Ashwaq by a Sufi named Ibn Arabi. The theory used is Riffaterre’s Semiotic theory. Written ada sources in the form of journals, books, and articles that are relevant to the topic of discussion. Tarjuman Al-Ashwaq contains poems that contain elements of love and longing, which are symbolized by the figure of a girl or woman who sparked controversy in the history of Islamic literary works because his poems were considered to contain the meaning of Ibn Arabi’s Sensual love for women. However, the results of the analysis show that the meaning carried out by the people at that time was wrong, Ibn Arabi only used women as a source of inspiration to represent his love and longing for Allah. Keywords: Ibn Arabi, Poetry, Tarjuman al-Ashwaq